Анализ особенностей экологического мониторинга атмосферного воздуха в зоне чрезвычайных ситуаций техногенного характера - Вамболь, Виола Владиславовна; Рашкевич, Александр Сергеевич; Рашкевич, Нина Владиславовна (НТУ "ХПИ", 2016)
Проведен анализ возможности организации дистанционного экологического мониторинга атмосферного воздуха в районах возникновения чрезвычайных ситуаций. Определены требования, имеющие важнейшее значение для проведения мониторинга в зоне чрезвычайных ситуаций техногенного характера, а именно, быстродействие получения данных контроля и возможность отбора представительной пробы. Установлено, что дистанционный лазерный мониторинг наиболее полно удовлетворяет необходимым требованиям и позволяет решить при помощи одного комплекта аппаратуры двуединую задачу – оперативного мониторинга газовых примесей и аэрозолей в условиях ЧС.

The analysis of possibility of organization of ecological RMON of atmospheric air is conducted in the districts of origin of emergencies. Requirements having a major value for realization of monitoring in the zone of emergencies of technogenic character are certain, namely, fast acting of receipt of control data and possibility of selection of representative test. In the zone of origin of emergency sampling can be produced only on a border by indignant and un indignant areas of atmosphere. Besides sampling to behave a traditional method to the noncommunicative volume round some point in space, that doesnot provide reliable information about current status of atmospheric air. Deciding this problem is possible the controlled from distance noncontact methods. It is set that laser RMON most full satisfies to the necessary requirements, because during realization of measuring a concentration along the route of sounding, and after the choice of a few directions the representatively "of test" increases repeatedly. Similarly the laser monitoring allow decide one in two task through one complete set of apparatus – operative monitoring of gas admixtures and aerosols in the conditions of emergency.
An analysis of features of the ecological monitoring of atmospheric air is in the zone of emergencies of technogenic character
Keywords: атмосферный воздух; экологический мониторинг; чрезвычайная ситуация; дистанционное зондирование; лазер; atmosphere; environmental monitoring; emergency; remote sensing; laser